2021
DOI: 10.1038/s41598-020-80627-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Fox genes in Schmidtea mediterranea reveals new families and a conserved role of Smed-foxO in controlling cell death

Abstract: The forkhead box (Fox) genes encode transcription factors that control several key aspects of development. Present in the ancestor of all eukaryotes, Fox genes underwent several duplications followed by loss and diversification events that gave rise to the current 25 families. However, few Fox members have been identified from the Lophotrochozoa clade, and specifically from planarians, which are a unique model for understanding development, due to the striking plasticity of the adult. The aim of this study was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 127 publications
2
33
0
Order By: Relevance
“…Strikingly, a recent example of 3D-DS under physiological conditions has been observed in the FoxP subfamily of transcription factors. Fox proteins are present in yeast and metazoans, and several evolutionary analyses have strongly suggested that these proteins were present in the ancestor of all eukaryotes [ 19 , 20 ]. Their absence in plants suggests that their origin is linked to a clade of unicellular organisms that gave rise to both the fungal and animal lineages [ 21 ].…”
Section: Molecular Evolution Towards 3d-ds In Human Foxp Transcription Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strikingly, a recent example of 3D-DS under physiological conditions has been observed in the FoxP subfamily of transcription factors. Fox proteins are present in yeast and metazoans, and several evolutionary analyses have strongly suggested that these proteins were present in the ancestor of all eukaryotes [ 19 , 20 ]. Their absence in plants suggests that their origin is linked to a clade of unicellular organisms that gave rise to both the fungal and animal lineages [ 21 ].…”
Section: Molecular Evolution Towards 3d-ds In Human Foxp Transcription Factorsmentioning
confidence: 99%
“…This increased diversity is reflected in the number of Fox proteins in different lineages from this branch, with mammalian genomes presenting at least 34 distinct Fox orthologs whereas only four genes are present in fungi [ 19 ]. In this regard, it has been suggested that the expansion of this protein family is the result of several duplications followed by loss and diversification events through multiple metazoan lineages during evolution [ 20 ]. This is the case for the emergence of the FoxS subfamily in the mammal and bird lineage divergence due to a duplication of a Fox gene from the original cluster present in basal Bilateria [ 24 ], which comprises the FoxC, FoxF, FoxL1, and FoxQ1 subfamilies [ 22 ].…”
Section: Molecular Evolution Towards 3d-ds In Human Foxp Transcription Factorsmentioning
confidence: 99%
“…In a previous study, we identified 3 paralogs within the FoxK family in S. mediterranea ( foxK1-2-3 ) ( Pascual-Carreras et al, 2021 ). In this study, we have inhibited the three foxK genes by RNAi, showing that RNAi of foxk1 generates the strongest phenotype ( Figure 1A ) ( Supplementary Figure S1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Forkhead box (Fox) genes belong to the “winged helix” superfamily of transcription factors, showing a Forkhead DNA-binding domain. Over 2,000 Fox proteins, phylogenetically classified into 25 families (A to S), have been identified in a number of species of fungi and metazoans ( Benayoun, Caburet, and Veitia 2011 ; Pascual-Carreras et al, 2021 ). Fox genes control essential processes such as cell death, cell cycle and cell differentiation during all stages of development and in adult tissues, although many members show a tissue/stage-specific expression and function ( Benayoun, Caburet, and Veitia 2011 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation